The ‘Live’ Gaze: A Neuromarketing and Eye-Tracking Analysis of Consumer Attention and Impulse Buying on Shopee Live and TikTok Shop in Indonesia - Muhammad Hasan; Henry Peter Paul; Darlene Sitorus; Despian Januandri; Brenda Jaleel (HM Publisher, 2025)
Livestream commerce (LSC) has redefined digital retail in Southeast Asia, with Indonesia as its most competitive market. The two dominant platforms, Shopee Live and TikTok Shop, leverage vastly different user interfaces and engagement philosophies—commerce-first versus content-first, respectively. However, the precise cognitive and affective mechanisms by which these platforms guide consumer attention and trigger impulse purchases remain empirically unexamined. This study employed a within-subjects laboratory experiment with 60 Indonesian consumers (aged 18-25). A multi-modal neuromarketing approach was used, synchronizing eye-tracking (ET) and electroencephalography (EEG) data. Participants viewed six 60-second LSC clips (three from Shopee Live, three from TikTok Shop) matched for product category. Key eye-tracking metrics (Total Fixation Duration, Time to First Fixation) were analyzed across predefined Areas of Interest (AOIs: Host Face, Product, Price, CTA Button, Chat). EEG data was processed to derive Frontal Alpha Asymmetry (FAA) for approach-avoidance motivation and Cognitive Load indices. Post-stimulus surveys measured Impulse Buying Urge (IBU). Significant differences emerged. Shopee Live generated longer Total Fixation Duration on the Host’s Face (M=12,500ms) and Price/Discount AOIs (M=8,800ms). Conversely, TikTok Shop elicited significantly faster Time to First Fixation on the Product (M=1,600ms) and CTA Button (M=2,800ms), and higher TFD on these AOIs. Neurologically, TikTok Shop produced significantly greater FAA (M=0.19 vs. 0.08), indicating higher approach motivation, and also induced a higher cognitive load. A multiple regression analysis revealed that the strongest predictors of IBU were TFD on the CTA Button, FAA, and TFD on the Host’s Face. TFD on the product itself was not a significant predictor. In conclusion, the findings demonstrate that platform architecture fundamentally shapes the